Comparing Azole Plasma Trough Levels in Lung Transplant Recipients: Percentage of Therapeutic Levels and Intrapatient Variability. Issue 2 (April 2017) - Stelzer, Daniela; Weber, Alexandra; Ihle, Franziska; Matthes, Sandhya; Ceelen, Felix; Zimmermann, Gregor; Kneidinger, Nikolaus; Schramm, Rene; Winter, Hauke; Zoller, Michael; Vogeser, Michael; Behr, Juergen; et al.
Abstract : Background: This study compared therapeutic azole plasma trough levels (APL) of the azole antimycotics itraconazole (ITR), voriconazole (VOR), and posaconazole (POS) in lung transplant recipients and analyzed the influencing factors. In addition, intrapatient variability for each azole was determined. Methods: From July 2012 to July 2015, 806 APL of ITR, VOR, posaconazole liquid (POS-Liq), and posaconazole tablets (POS-Tab) were measured in 173 patients of the Munich Lung Transplantation Program. Therapeutic APL were defined as follows: ITR, ≥700 ng/mL; VOR, 1000–5500 ng/mL; and POS, ≥700 ng/mL (prophylaxis) and ≥1000 ng/mL (therapy). Results: VOR and POS-Tab reached the highest number of therapeutic APL, whereas POS-Liq showed the lowest percentage (therapy: ITR 50%, VOR 70%, POS-Liq 38%, and POS-Tab 82%; prophylaxis: ITR 62%, VOR 85%, POS-Liq 49%, and POS-Tab 76%). Risk factors for subtherapeutic APL of all azoles were the azole dose (ITR, P < 0.001; VOR, P = 0.002; POS-Liq, P = 0.006) and age over 60 years (ITR, P = 0.003; VOR, P = 0.002; POS-Liq, P = 0.039; POS-Tab, P < 0.001). Cystic fibrosis was a significant risk factor for subtherapeutic APL for VOR and POS-Tab (VOR, P = 0.002; POS-Tab, P = 0.005). Double lung transplantation (LTx) was significantly associated with less therapeutic APL for VOR and POS-Liq (VOR, P = 0.030; POS-Liq, P < 0.001). Concomitant therapy with 80 mg pantoprazole led to significantly fewer therapeutic POS APL as compared to 40 mg (POS-Liq, P = 0.015; POS-Tab, P < 0.001). VOR displayed the greatest intrapatient variability (46%), whereas POS-Tab showed the lowest (32%). Conclusions: Our study showed that VOR and POS-Tab achieve the highest percentage of therapeutic APL in patients with LTx; POS-Tab showed the lowest intrapatient variability. APL are significantly influenced by azole dose, age, cystic fibrosis, type of LTx, and comedication with proton-pump inhibitors. Considering the high number of subtherapeutic APL, therapeutic drug monitoring should be integrated in the post-LTx management.